The little-known history of cleanliness and the forgotten pioneers of handwashing - Poczai, Peter; Karvalics, László Z. (Frontiers in Public Health, 2022)
Handwashing is a simple method for preventing the spread of pathogens. It is now common practice, but this was not always the case. Advocating for it often costed a doctor his career in the 1840s. Hospitals in the early 1800s had little idea of the significance of hygiene; thus, they were often mocked as disease-producing incubators or as “houses of death.” Many of the ill and dying were kept on wards with no ventilation or access to clean water; hospitals were found to offer only the most basic care. The mortality rate for patients admitted to hospital was three to five times greater than that for individuals cared for at home. Doctors did not routinely wash their hands until the mid-1800s, and they would proceed straight from dissecting a corpse to delivering a baby, providing the basis for the spread of puerperal fever. Despite advances in modern medicine, healthcare providers still face the issue of infection outbreaks caused by patient care. While the body of scientific data supporting hand hygiene as the key strategy to prevent the spread of pathogens is substantial, we highlight that achieving this crucial, long-awaited breakthrough was a hard task through history.